Pengaruh Produk dan Harga Terhadap Minat Beli Ulang dengan Kepuasan Sebagai Variable Intervening pada Catering Pondok Harmony di Kabupaten Sanggau - Feby Kusuma; Erna Listiana; Ramadania (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to determine the effect of product and price on customer satisfaction and repurchase intention at Pondok Harmony Catering in Sanggau Regency. This study is an associative study. The population in this study were all consumers of Pondok Harmony Catering, with a sample of 100 people. The sampling technique used was purposive sampling. The data analysis technique used in this study was structural equation modeling (SEM). The results showed that the product variable had a positive and significant effect on satisfaction while the product had a positive but insignificant effect on repurchase intention. The price variable had a positive but insignificant effect on satisfaction while the price variable had a positive and significant effect on repurchase intention. The satisfaction variable had a positive and significant effect on repurchase intention. The product variable had a positive and significant effect on repurchase intention through satisfaction and the price variable had a positive and significant effect on repurchase intention through satisfaction.